2015
DOI: 10.1038/ni.3268
|View full text |Cite
|
Sign up to set email alerts
|

Kinases Mst1 and Mst2 positively regulate phagocytic induction of reactive oxygen species and bactericidal activity

Abstract: Summary Mitochondria need to be juxtaposted to phagosomes to synergistically produce ample reactive oxygen species (ROS) in phagocytes for pathogens killing. However, how phagosomes transmit signal to recruit mitochondria remains unclear. Here, we report that the kinases Mst1 and Mst2 function to control ROS production by regulating mitochondrial trafficking and mitochondrion-phagosome juxtaposition. Mst1 and Mst2 activate Rac GTPase to promote Toll-like receptor (TLR)-triggered assembly of the TRAF6-ECSIT com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(240 citation statements)
references
References 49 publications
6
232
0
2
Order By: Relevance
“…As shown in Fig. 3A, TRAF6 in mock-infected cells displayed a diffused staining pattern in the whole cell, in agreement with the previous reports (27,28). Few autophagic vacuoles (i.e., GFP-LC3 puncta) could be detected in mock-infected cells.…”
Section: Suppression Of Traf6 Expression By Hcvsupporting
confidence: 80%
“…As shown in Fig. 3A, TRAF6 in mock-infected cells displayed a diffused staining pattern in the whole cell, in agreement with the previous reports (27,28). Few autophagic vacuoles (i.e., GFP-LC3 puncta) could be detected in mock-infected cells.…”
Section: Suppression Of Traf6 Expression By Hcvsupporting
confidence: 80%
“…In addition to ROS production by the NADPH oxidase complex, it has been shown that mitochondria-generated ROS is important for phagocyte-mediated bacterial killing, although L. monocytogenes was not used in this study (79). Furthermore, efficient phagosome localization with the mitochondria, mediated by the Mst1 and Mst2 kinases, is required for optimal induction of ROS downstream of TLR signaling, and mice lacking both Mst1 and Mst2 show increased susceptibility to L. monocytogenes compared to wild-type mice (80). …”
Section: Neutrophil Function During L Monocytogenes Infectionmentioning
confidence: 99%
“…However, the regulation of YAP and TAZ by stress signals, such as energy stress, endoplasmic reticulum stress, and hypoxia, has been characterized only in the last couple of years, although activation of MST1/2 by a high concentration of sodium arsenite or heat shock was observed a long time ago (Taylor et al 1996). MST1/2 are also activated by hydrogen peroxide and are involved in cellular oxidative stress responses (Lehtinen et al 2006;Geng et al 2015). On the other hand, YAP physically interacts with FOXO1 and activates FoxO1-mediated transcription of catalase and MnSOD genes and subsequently reduces oxidative stress and ischaemia/reperfusion (I/R)-induced injury in the heart (Shao et al 2014), implicating a physiological role of YAP in reactive oxygen species (ROS) scavenging.…”
Section: Stress Signalsmentioning
confidence: 99%